The prerequisites for the development of type 2 diabetes or prediabetes in rats fed a high-fat diet - A. G. Portnychenko; M. I. Vasylenko; R. B. Aliiev; M. G. Kozlovska; M. O. Zavhorodnii; P. K. Tsapenko; K. V. Rozova; V. I. Portnichenko (Regulatory Mechanisms in Biosystems, 2022)
It is known that the pathogenesis of type 2 diabetes in humans is based on two main factors – insulin resistance and inappropriate secretory activity of β-cells of the pancreas. In animals, the role of these mechanisms has not been clearly characterized, and the differences in the manifestations of experimental diabetes under the same conditions are not sufficiently substantiated. In order to study the prerequisites and mechanisms of the development of experimental type 2 diabetes or prediabetes under lipid overload, 6-month-old male Wistar rats were fed a high-fat diet for 4 weeks; after 2 weeks of the experiment, 20 or 25 mg/kg of streptozotocin was administrated. The development of insulin resistance was assessed using the insulin tolerance test. We evaluated the dynamics of glycemia in animals, subcellular signs of liver steatosis, and determined expression of the precursor and mature protein SREBP-1 by immunoblotting. It was found that in rats fed with a high-fat diet during the 2–4th weeks of the experiment, regardless of the administration of streptozotocin, stable insulin resistance and symptoms of prediabetes were detected. The severity of carbohydrate metabolism lesion, which appeared as type 2 diabetes or prediabetes after streptozotocin administration, depended on the level of hepatosteatosis due to high-fat diet, whereas the dose of streptozotocin influenced severity of type 2 diabetes. The use of a high-fat diet led to increased processing and activation of SREBP-1, which was clearly inhibited in type 2 diabetes. Therefore, the level of lipid infiltration of the liver and deregulation of the transcription factor SREBP-1 are risk factors defining development of type 2 diabetes or prediabetes in experimental rats with lipid overloading. Changes in the maturation of SREBP-1 with the use of a high-fat diet confirm that insulin resistance in rats revealed β-cell dysfunction, which closely approximates the mechanisms of experimental type 2 diabetes to main pathways in humans. At the same time, the predisposition to β-cell dysfunction can be a prerequisite that determines compensatory reserves for maintaining carbohydrate and lipid homeostasis under the influence of lipid load in both humans and laboratory animals.